ESTRO recommendations on preoperative radiation therapy in breast cancer: current and future perspectives – Endorsed by ASTRO - Zamagni, Alice; Montero Luis, Angel; Mjaaland, Ingvil; Chirila, Monica Emilia; Ciervide, Raquel; Machiels, Melanie; Ratosa, Ivica; Van Den Bongard, Desiree H.J.G.; Aznar, Marianne; Boersma, Liesbeth J.; Coles, Charlotte E.; Corradini, Stefanie; et al. (Radiotherapy and Oncology, 2026)
Background and purpose: Preoperative radiation therapy (RT) for breast cancer is not a novel concept, though available data are insufficient to translate current knowledge into clinical practice. Nonetheless, potential advantages of this approach are emerging in multiple scenarios, incorporating increasing treatment personalization and technological improvements in RT. This paper aims to synthesize and summarize the literature on preoperative RT in distinct breast cancer treatment settings, providing perspectives based on existing evidence and gaps in knowledge. Methods: The ESTRO Breast subgroup proposal for elaborating perspectives on preoperative RT was approved by the ESTRO Guidelines Committee, and a panel of experts in the field was identified. Four working groups were created, focusing on the different clinical settings where preoperative RT has been investigated: patients with early-stage breast cancer at low risk of recurrence, patients with breast cancer at high risk of recurrence, and patients with an indication for mastectomy. The fourth group focused its search on cross cutting themes, such as preclinical and translational aspects, radiobiology, RT techniques and quality assurance. After a literature search including the identification of key points and gaps in the literature, the four working groups presented their findings and perspectives were formulated, discussed and approved by the panel. Results: Overall, 27 phase I and phase II studies enrolling patients from the year 2000 onward were considered, collecting data such as RT dose and fractionation, clinical outcomes, and complications rates. The expert panel stated perspectives for the different clinical scenarios based on available evidence and current gaps in knowledge, to be addressed by future clinical research. Conclusion: Given the current lack of clinical data to support the development of formal guidelines, we present our perspectives, which can be useful for implementing new clinical trials and research projects, overcoming current limitations, and potentially generating high-quality practice-changing data, introducing preoperative RT in specific breast cancer treatment settings in the future.
CRIS-Team Scopus Importer:2025-11-21
Keywords: Breast cancer; Clinical trials; ESTRO; Preoperative radiation therapy; Research